Association of Symptoms of Obstructive Lung Disease and All‐Cause Mortality in Older Adult Smokers. Issue 10 (27th June 2019) - Opina, Maria Theresa D.; Nicklas, Barbara J.; Lovato, James F.; Files, Daniel C.; Kritchevsky, Stephen B.; Moore, Wendy C.
Abstract : OBJECTIVES: This study aims to investigate the impact of respiratory symptoms in current and former smokers with and without obstructive lung disease (OLD) on all‐cause mortality. DESIGN: Secondary analysis in a prospective cohort (the Health, Aging and Body Composition study). SETTING: Memphis, Tennessee, and Pittsburgh, Pennsylvania. PARTICIPANTS: Black and white men and women with a history of current and former smoking (N = 596; 63% male and 37% female) aged 70‐79 years followed for 13 years. Participants were categorized into 4 mutually exclusive groups based on symptom profile and forced expiratory volume in the 1st second to forced vital capacity ratio. The groups were Less Dyspnea‐No OLD (N = 196), More Dyspnea‐No OLD (N = 104), Less Dyspnea‐With OLD (N = 162), and More Dyspnea‐With OLD (N = 134). MEASUREMENTS: All‐cause mortality. RESULTS: Overall, 53% in Less Dyspnea‐No OLD, 63% in More Dyspnea‐No OLD, 67% in Less Dyspnea‐With OLD, and 84% in More Dyspnea‐With OLD died within the 13‐ year follow up period (log‐rank χ 2 = 44.4, P < .0001). The hazard ratio was highest for participants with OLD, both with (HR =1.91, 95% CI 1.44 ‐ 2.54; P < .0001) and without dyspnea (HR = 1.52, 95% CI 1.15 ‐ 2.02; p = .004). Participants without OLD but with dyspnea had a similar risk of death to subjects who had OLD but fewer symptoms. CONCLUSIONS: OLD is associated with high risk of death with different risk profiles based on symptom group. Patients with symptoms of shortness of breath without OLD should be considered an at‐risk group given their similar mortality to those with OLD with minimal symptoms. J Am Geriatr Soc 67:2116–2122, 2019